Hungarian Monitoring, 17 October 1989 . [Magyar rádiófigyelő], 1989. október 17 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Foreign Minister Baker urges support for Eastern European countries - Reports from the GDR - Azerbaijan-Armenian conflicts - USSR: Brandt in Moscow; Yeltsin Domestic Affairs: - Parliament discusses the constitutional court, audit office, proposed regulations on electing representatives and president of the republic - Alliance of Free Democrats (SZDSZ) collect signatures - Relations between Hungarian Socialist Party (MSZP) and Hungarian Socialist Workers' Party (MSZMP) - World Exposition - Tender for construction of the National Theater - Refugee camp in Csillebérc Külpolitika: - Baker külügyminiszter a kelet-európai országok támogatását szorgalmazta - NDK-beli beszámolók - Azerbajdzsán-örmény konfliktusok - SZU: Brandt Moszkvában; Jelcin Belpolitika: - Az Országgyűlés tárgyalt az alkotmánybíróságról, a számvevőségről, a képviselők és a köztársasági elnök választásáról szóló jogszabály javaslatokról - SZDSZ aláírásgyűjtési akció - MSZP és az MSZMP viszonya - Világkiállítás - A Nemzeti Színház megépítésére kiírt pályázat - Csillebérci menekülttábor